Pregnancy loss after in vitro fertilization and related factors - Son, Hoang Ngoc; Tam, Le Minh; Phuong, Nguyen Pham Quynh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Introduction: After getting pregnant by in vitro fertilization (IVF), pregnancy loss is one factor that prevents the baby from being born. An estimated 80% of pregnancy loss occurs in the first trimester, which is higher than in the natural pregnancy. The reason is said to be that the age of women receiving fertility treatment is often higher, leading to ovarian reserve, and decreased oocyte quantity and quality. However, studies on the pregnancy loss rate in Vietnam are still hard, and global studies still do not provide a complete consensus on the factors affecting this rate. This study aims to evaluate the pregnancy loss rate 12 weeks after in vitro fertilization and find some related factors. Methods: A cross-sectional descriptive study in embryo transfer patients after IVF treatment at Department of Assisted Reproduction in Hue Central Hospital was done from January 2020 to May 2021. Criteria for selection are pregnancy after embryo transfer (βhCG ≥ 25 UI/L after 14 days of embryo transfer) and having ultrasound monitoring up to 12 weeks gestation. Exclusion criteria include donor eggs, multifetal pregnancy reduction and ectopic pregnancy or hydatidiform mole. Results: There are 42 cases of pregnancy loss up to 12 weeks gestation in 133 pregnancies (βhCG ≥ 25 UI/L), equivalent to 31.6%. Among them were 9 cases of biochemical pregnancy, and 33 cases of pregnancy loss when having clinical pregnancy. The rate of at least one developing fetus to 12 weeks gestation is 102/133, equivalent to 76.7%. The pregnancy loss rate was statistically significantly lower in the group with endometriosis ≥ 10 mm before the embryo transferring date. Conclusion: Pregnancy loss after IVF is an issue that needs to be studied with a larger sample size to deeply understand the influencing factors to optimize the outcome of embryo transfer.